A Theoretical Study of Myricetin and Its Derivates towards the Corrosion of the Mild Steel Using Density Functional Theory - , Azuxetullatif (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2025)
The effect of myricetin and its derivatives (myricetin 3-O-L-rhamnoside (myricitrin), and myricetin 3-alpha-L-arabinouranoside) towards corrosion on the metal surfaces had been studied using density functional theory (DFT) at the B3LYP/6-31G (d, p). Quantum chemical parameters such as, orbital energies (EHOMO, ELUMO), energy gap (ΔE), dipole moment (µ) were calculated from optimizing results of molecule A, B and C compounds. The gap energy (ΔE), ionization potential (I), electron affinity (A), electronegativity (χ), hardness (η), softness (σ), transferred electrons fraction (ΔN), electrophilicity index (ω), interaction energy (ΔEint) and binding energy (ΔEbinding) were determined from EHOMO dan ELUMO value.